Pro-Choice Rally at State Building Plaza and Surrounding Area - Watkins, Howard::::::::: (1989)
Close-up of standing crowd facing stage: in middle: Ken Clarke, Fresno Mayor Karen Humphrey, Val Weston holding sign and others